Those Who Know Don't Say : The Nation of Islam, the Black Freedom Movement, and the Carceral State - Felber, Garrett (Book collections on Project MUSE., 2020)
"Challenging incarceration and policing was central to the postwar Black Freedom Movement. In this ... political and intellectual history of the Nation of Islam, Garrett Felber centers the Nation in the Civil Rights Era and the making of the modern carceral state. The book examines efforts to build broad-based grassroots coalitions among liberals, radicals, and nationalists to oppose the carceral state and struggle for local Black self-determination. It captures the ambiguous place of the Nation of Islam specifically, and Black nationalist organizing more broadly, during an era which has come to be defined by nonviolent resistance, desegregation campaigns, and racial liberalism"--